Privatisasi: Kinerja Keuangan dan Distribusi Laba (Analisis Kritis Pada Pt Garuda Indonesia (Persero) Tbk) - Widyastuti, Aviani; Irianto, Gugus; Achsin, Mohammad (Universitas Muhammadiyah Malang)
This study aims to analyze the privatization policy of PT Garuda Indonesia (Persero) Tbk. The critical paradigm using the Political Economy of Accounting (PEA) theoretical framework becomes a tool used to describe pre-privatization and post-privatization performance. The results showed that post-privatization Garuda Indonesia’s financial performance tended to decrease. While the distribution of profits (wealth) to employees and shareholders (investors and government) is not done with the maximum. Distribution is only visible to employees and creditors but the increase is not due to the value distributed but it’s because of the increase in the number of employees and the main requirement of Garuda Indonesia related to business expansion.